The impacts of monsoon and dry seasons on physical water quality changes and farmed Asian seabass Lates calcarifer (Bloch, 1790) mortality at Sri Tujuh lagoon, Tumpat, Kelantan, Malaysia - Abdullah, Hamidi H.; E. Rak, Aweng; Lee, S. Wei (2018)
This study aimed to monitor the water quality in Sri Tujuh lagoon during monsoon and dry seasons, as well as the impact of the two seasons on the production of Asian seabass (Lates calcarifer). The water quality parameters such as temperature, pH, dissolved oxygen (DO), salinity, conductivity, turbidity and total dissolved solid of Sri Tujuh lagoon were assessed using water samples collected from 13 sampling points at 1ft, 4ft and 7ft water depth during dry season (March-August 2014) and monsoon (September-November 2014). Fish mortality was recorded from Asian seabass farmers in the lagoon. Water quality data during dry seasoon and monsoon was compared using T-Test and data from 3 different depths was analysed by using One Way Anova followed by Tukey test at p < 0.05. The water parameters in dry season, monsoon season, combination of dry and monsoon season were subjected to Pearson correlation analysis separately and a matrix was tabulated. Water parameters were also subjected to cluster analysis by using Ward’s method with squared Euclidean distances as a measure of similarity. In the present study Ward’s method was used ANOVA followed by Tukey post hoc in order to minimize the sum of squares. The result was represented by a dendrogram. The findings of the present study showed water parameters such as DO, salinity and turbidity were significantly different between dry and monsoon seasons. However no significant difference was found in term of fish mortality. The water parameters of Sri Tujuh lagoon during the study were as follow: temperature 29.4-33.3 oC; pH 7.0-9.3; DO 0.8-6.8 mg L -1 ; salinity 10.7-31.3 ppt; conductivity 17.5-50.5 µs cm-1 ; turbidity 5.4-59.8 NTU; TDS 23.3-32 ppt. The fish mortality was recorded ranging from 9.3 to 15.5% from March to November, 2014. The positive and significance (p < 0.01) correlation was recorded between temperature and pH (0.434), temperature and DO (0.472), DO and pH (0.315), salinity and pH (0.615), conductivity and pH (0.595), conductivity and salinity (0.992), TDS and pH (0.340), TDS and salinity (0.322) and TDS and conductivity (0.322). Fish mortality showed no correlation with all water parameters changing in the whole study at Sri Tujuh lagoon. Based on the water parameter records from 13 sampling stations, the sampling stations can be divided into 5 clusters. Cluster 1 possesses the greatest number of stations namely S3, S4, S6, S7, S8, S11 and S12 whereas Cluster 2 has S1, S10 and S13. Only one station was found in the Cluster 3 (S5), Cluster 4 (S2) and Cluster 5 (S9). Based on the findings of the present study, Sri Tujuh lagoon can be considered as one of the best places to conduct aquaculture activities in Kelantan.